ANALISIS DISTRIBUSI MINAT MAHASISWA PADA KONSENTRASI INFORMATIKA MENGGUNAKAN PENDEKATAN DATA-DRIVEN DECISION MAKING - Fathoni Mahardika; Fidi Supriadi; Agun Guntara (INTI Nusa Mandiri, 2025)
In the digital era, higher education institutions face the challenge of aligning the curriculum with the dynamic demands of the industry. This research aims to identify patterns of student interest in choosing specialization concentrations in the Informatics Study Program (S1), Universitas Sebelas April, using a data-driven decision-making approach. The study involved 133 5th semester students out of a total population of 500 students in the Computer Science program at Sebelas April University. The respondents were selected because they were at the relevant stage of study to determine the specialization concentration, the results of which provide important recommendations for curriculum optimization and resource allocation.Student specialization survey data were analyzed using descriptive statistics, data visualization, and trend analysis to provide data-driven insights to support more efficient academic planning. The results showed that the concentration of "Computer Science, Software, and Intelligent Systems" was more desirable than "System Security and Computer Networks".